Effective Ionic Resistance in Battery Separators. (9th September 2015) - Hattendorff, Johannes; Landesfeind, Johannes; Ehrl, Andreas; Wall, Wolfgang A.; Gasteiger, Hubert A.
Abstract : The ionic transport properties of battery materials such as separators can be measured by AC impedance. We show data from two measurement setups and demonstrate how a reliable measurement of the high frequency resistance and thus tortuosity of typical separators can be achieved.